PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENGANALISA KEEFEKTIFAN BELAJAR DAN KEMAMPUAN MENDENGAR BAHASA INGGRIS MAHASISWA KEPERAWATAN - Yulis Setyawati; Retno Purwani; Ayu Pratiwi (Nusantara Hasana Journal, 2022)
Audio visual media is a learning aid that produces sound effects (audio) and images (visual) as learning media, this is to make it easier for students to understand it. Based on a preliminary study conducted on level 3 nursing students at the Yatsi Madani University campus, it was found that the lecturer did not provide visual and listening sections to students to practice their listening skills. The purpose of research to determine the extent to which audio-visual media is effective in teaching and learning English. This research design uses a qualitative design with a case study approach. The population in this study were several level 3 nursing students at Yatsi Madani University, the participant determination technique used was purposive sampling technique with 8 students participating. The results of this research that the application of audio visual media in English learning is effectively used, it can be seen from the results of interviews, the results of the pretest when using audio media only 25% of students get results above the pass limit value that has been determined by the researcher, and after the post test there is a significant increase by 75% of students who get scores above the pass mark.